2015
DOI: 10.1039/c4pp00392f
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the UV absorption of 4-methylbenzylidene camphor: from the UVB to the UVA region

Abstract: In this study, a theoretical approach was used to study the UV absorption of the UVB filter, 4-methylbenzylidene camphor. The main objective of this work was to design new UVA filters based on this rather photo-stable compound, so that photo-degradation in this UV region can be avoided without the use of other molecules. This objective was achieved by the simultaneous addition of two appropriate substituents, which led to red-shifts of up to 0.69 eV while maintaining appreciable oscillator strength. Also, usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The percentage of initial UVA PF and AUC values range from 103.5 to 87.0% and 94.0 to 79.6% respectively. Especially compound 3d is characterized by functional photostability very similar to that of 4-MBC which is considered a photostable UV-filter [48]. The analysis of chromatograms and mass spectra of selected compounds indicates that in macrogol formulations the compounds behave as in methanol solutions.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of initial UVA PF and AUC values range from 103.5 to 87.0% and 94.0 to 79.6% respectively. Especially compound 3d is characterized by functional photostability very similar to that of 4-MBC which is considered a photostable UV-filter [48]. The analysis of chromatograms and mass spectra of selected compounds indicates that in macrogol formulations the compounds behave as in methanol solutions.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the attention that nowadays is given to protection against solar radiation and the potential of photothermal materials, it is not surprising that over the years increasingly more studies have been reported that focus on these aspects. The development of spectroscopic techniques that enable such studies over a wide range of wavelengths, encompassing time scales ranging from femtoseconds to days and longer, and under a large variety of environmental conditions [18][19][20][21][22][23][24][25][26][27] in combination with advanced quantum chemical calculations [28][29][30][31][32][33] has from this point of view contributed significantly to the body of knowledge that is currently available.…”
Section: Introductionmentioning
confidence: 99%
“…Computationally, to the best of our knowledge, there are two computational works that focus on exploring ground‐state structures and absorption spectra of 4MBC . The photophysical mechanism of 4MBC is not studied.…”
Section: Introductionmentioning
confidence: 99%